Analisis dan Implementasi Pengelolaan Keuangan pada Yayasan - Anwar SA; Fadli Faturrahman (MAMEN: Jurnal Manajemen, 2023)
One non-profit organization that exists in Indonesia is a foundation, a legal entity that is not profit-oriented. Accountability itself is a form of responsibility towards the provider of resources (donors). The financial reporting of a foundation refers to Interpretation of Financial Accounting Standards (ISAK) No.35. The purpose of this research is to analyze the implementation of accountability and the financial management implementation of Yayasan Al Ashola Al Islamiyah Sumbawa in accordance with ISAK 35 guidelines. The analysis tools used include interview results, documentation, and financial reports of the Foundation. The research results show that the research object has not implemented Accountability in financial reporting because only two indicators can be applied by the Foundation. As for financial reporting, the research object has not implemented it in accordance with the Financial Accounting Standards ISAK 35 due to several factors such as the Foundation's young age, financial experts who are unfamiliar with ISAK 35, and the Foundation has never conducted bookkeeping and inventory of assets. The financial reports owned by the Foundation are still limited to simple reports such as cash inflows and outflows.